2020
DOI: 10.3390/medicina56040177
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Risk Factors for Diabetic Retinopathy in Type 1 and Type 2 Diabetes Mellitus Patients in North-East Poland

Abstract: Background and Objective: Nowadays, diabetes is one of the main causes of blindness in the world. Identification and differentiation of risk factors for diabetic retinopathy depending on the type of diabetes gives us the opportunity to fight and prevent this complication. Aim of the research: To assess differences in the risk factors for diabetic retinopathy in type 1 and type 2 diabetes mellitus patients in Warmia and Mazury Region, Poland. Materials and Methods: Risk factors for diabetic retinopathy (DR) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
6
4
0
Order By: Relevance
“…In addition, our study also indicates that tobacco strongly advanced the progression of DR. A similar conclusion was found by Uruska et al, (2014) regarding patients with T1D. Other authors also established a causal link between smoking and the incidence of DR (Matuszewski et al, 2020;Campagna et al, 2019). Interestingly, body corpulence elevated the probability of DR in our study population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, our study also indicates that tobacco strongly advanced the progression of DR. A similar conclusion was found by Uruska et al, (2014) regarding patients with T1D. Other authors also established a causal link between smoking and the incidence of DR (Matuszewski et al, 2020;Campagna et al, 2019). Interestingly, body corpulence elevated the probability of DR in our study population.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showed significant effects of age and duration of diabetes on the presence of DR. The findings concord with Matuszewski et al who found that aged patients (≥ 30 years) with long-lasting diabetes (≥ 15 years) had higher risk to develop more severe DR (Matuszewski et al, 2020). The results are also consistent with previous studies in the literature (Carbonell et al, 2018;Rajalakshmi et al, 2014;Araszkiewicz et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…DR is a persistent ocular fundus condition that accounts for 80% of visual loss in individuals with diabetes and therefore affects the quality of life, as well as elevating the financial burden on society [51,52]. Risk factors of diabetic retinopathy include its duration, the presence of diabetic nephropathy, neuropathy, foot ulcer and amputation, along with hypertension, the level of cholesterol and triglyceride in the serum, fasting blood glucose, the level of HbA1c and the age of the patient [53].…”
Section: Risk Factors Of Diabetic Retinopathymentioning
confidence: 99%
“…Moreover, patients did not recognize retinopathy and were not diagnosed with it at an early stage since early DR does not significantly affect their eyesight. Matuszewski et al (2020) found that hyperglycemia is a major risk factor and a modifiable factor for DR, regardless of diabetes type. Kumari et al (2019) reported that patients with poor blood sugar control have a quadrupled risk of developing DR.…”
Section: Discussionmentioning
confidence: 96%